The Earth transformed : an untold history - Frankopan, Peter (Alfred A. Knopf, 2023)
"Global warming is one of the greatest dangers mankind faces today. Even as temperatures increase, sea levels rise, and natural disasters escalate, our current environmental crisis feels difficult to predict and understand. But climate change and its effects on us are not new. In a bold narrative that spans centuries and continents, Peter Frankopan argues that nature has always played a fundamental role in the writing of history. From the fall of the Moche civilization in South America that came about because of the cyclical pressures of El Niño to volcanic eruptions in Iceland that affected Egypt and helped bring the Ottoman empire to its knees, climate change and its influences have always been with us"--